The Effect of Atmospheric Aerosol on the Net Solar Radiation Balance of the Surface-Lower Atmospheric System - Barker, Howard (My University, 1985)
A simple method for computing the effect of atmospheric aerosol on the net solar radiation balance of the surface-lower atmosphere system is presented. It was found that in clear sky conditions at Goose Bay, Toronto and Winnipeg, for the period 1977 -1982, the presence of aerosol made the systems 10 -20% more efficient at absorbing radiation than if the aerosol was absent. Furthermore, surface albedo is shown to be the most important parameter governing the effect of aerosol on the net solar radiation balance in an aerosol system, while the effect of volcanic aerosol produced by El Chichon had a minor influence on the net solar radiation balance.
Page 7 was mistyped as being page 8. All content present is in logical order.
Keywords: atmospheric aerosol; solar radiation; surface-lower atmosphere system; Toronto; Winnipeg